The boy who followed Ripley - Highsmith, Patricia 1921-1995 (Vintage crime/Black Lizard., 1993)
"In this quietly terrifying exploration of trust and friendship, a troubled young runaway arrives in Villeperce. And when, on the boy's behalf, Tom Ripley is drawn from his lovely estate in the French countryside to Berlin's seamy underworld and into a kidnapping plot that requires the most bizarre methods--and sinister acumen--for intervention, the icily amoral Ripley is transformed into a generous and compassionate protector."--Back cover.